Pemanfaatan Teknologi Informasi Untuk Meningkatkan Kuliatas Pembelajaran Di Sekolah Menengah Pertama Negeri 1 Sarolangun - Pirwanto; Kemas Imron Rosadi; Sodiah (Jurnal Kependidikan, 2025)
In today’s digital era, the integration of information technology in education has become an inevitable necessity. Information technology offers opportunities for educators to create learning environments that are more engaging, innovative, and tailored to students' needs. This study aims to describe the use of technology in enhancing the quality of learning at SMP Negeri 1 Sarolangun. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The data analysis process involved data collection, reduction, presentation, and conclusion drawing or verification. The findings reveal that prior to the integration of technology, the learning process was largely dominated by traditional methods, resulting in passive student engagement and limited participation. After the implementation of technology, there was a significant improvement in learning quality, marked by the use of digital devices and educational applications that enriched students’ learning experiences, facilitated better understanding of the material, and increased student participation. The successful implementation of technology was supported by school principals, teachers, parents, and the government. However, several challenges remained, including limited access to devices, unstable internet connectivity, and teachers' limited technical skills in using technology. Students also faced challenges such as the lack of devices at home and limited access to online materials. Nevertheless, the use of technology has proven effective in improving the quality of learning, classroom management, and social interaction between teachers and students. Therefore, continuous efforts are needed to overcome infrastructure limitations and enhance the digital competence of all stakeholders involved.